A perceptual analysis of the employees in the Nauts and Vectors Company Incorporation in terms of the manner of implementation of the disciplinary action towards the attainment of industrial peace in the company - Dahari, Nina Aliyah Buenafe., Dimaculangan, Angelica Denise Aguja., Lucena, Sheena Karyl De Vera., Mascariñas, Krystal Bell Sarmiento., Mercado, Dianne Nicole., Tesarra, Rovic Ivan Villanueva 4 0 16; 5
Introduction Today's businesses operate in a highly dynamic environment, with rapid technological advancements requiring the application of continuous improvement to goods and services, as well as the performance of the employees. Organizations are composed of employees who collaborate and depend on one another to achieve organizational goals. There is no such thing as a firm without rules and regulations. Employers must communicate their requirements. Employees should understand what conduct is acceptable, how they are expected to perform, and what consequences will be imposed if they fail to meet their employer's expectations. Negative attitudes inside a company might result in numerous difficulties. That's why the company needs disciplinary action in response to employee misconduct, rule violations, or poor performance. The Nauts and Vectors Company, Inc., or NAVCO, mounts integrated marketing campaigns with a strong focus on digital. With their nationwide network of dealers, customers, and retail partners, they help brands penetrate strategic channels across the Philippines. NAVCO is the official distributor of Garmin smart wearables in the Philippines is the chosen company of this study. This study will analyze the perceptions of the employees in NAVCO regarding the manner of implementation of disciplinary action in their company in attaining the industrial peace in the workplace.
Business Research: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2